SOCIAL GUIDELINES IN THE MODERN FINANCIAL SYSTEM OF KAZAKHSTAN - Dzharikbaeva Dinara Turarovna,; Turmakhanbetova Galia Atabekovna,; Ishanova Ruslana Kuanyshevna, (Academic Journal of Physical and Chemical Sciences, 2020)
Social guidelines in the modern financial system of Kazakhstan are a very relevant topic, since this relationship is straightforward and ambiguous. Successful functioning of the state is impossible without the creation of an effective financial system. Indeed, the growth and stability of the state economy depends on how efficiently the financial system functions. According to the authors, Kazakhstan has all the prerequisites for creating the basis for social protection of the population. Therefore, strengthening the financial system and ensuring that the national economy enters the path of growth and social development is an urgent and important problem today. A high level and quality of life is a requirement of the time, without it, the development of the state is impossible. Ensuring a high level and quality of life is beneficial both for the population, business, and for the government.